City-Wide Inclusive Water Supply : Refocusing on Off-Grid Solutions for Addressing Sustainable Development Goal 6.1 - Misra, Smita; Kingdom, Bill (World Bank, Washington, DC, 2019)
The objective of this report is to better understand the challenges of meeting Sustainable Development Goal 6.1 from the perspective of off-grid services currently being used by a large and increasing proportion of the urban population. For this assessment, two key distinct areas with high current or potential off-grid service dependence have been analyzed-core urban areas and peri-urban areas. The core urban areas comprise primarily the slums or poor population pockets that have not been covered by conventional piped systems. The peri-urban areas are characterized, on the one hand, by the displacement of population, industries, and services from the city center to the periphery, resulting in economically rich growth centers, while on the other hand, by slow or poor absorption of these areas into provisioning of basic urban facilities or services by local bodies, resulting in high dependence on independent off-grid service providers. At its heart, this is a scoping study which can provide the foundation for follow-on work that would lead to "reimagined" off-grid service delivery arrangements that complement piped systems-not as a sub-optimal solution but as an acceptable alternative that will ensure all urban residents have "equitable access to safe and affordable drinking water